2015
DOI: 10.1021/ja510602z
|View full text |Cite
|
Sign up to set email alerts
|

Improved PeT Molecules for Optically Sensing Voltage in Neurons

Abstract: VoltageFluor (VF) dyes have the potential to optically measure voltage in excitable membranes with the combination of high spatial and temporal resolution essential to better characterize the voltage dynamics of large groups of excitable cells. VF dyes sense voltage with high speed and sensitivity using photoinduced electron transfer (PeT) through a conjugated molecular wire. We show that tuning the driving force for PeT (ΔGPeT + w) through systematic chemical substitution modulates voltage sensitivity, estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
145
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(164 citation statements)
references
References 42 publications
9
145
1
2
Order By: Relevance
“…2C). As predicted, and as demonstrated for previous classes of PeT-based voltage sensors (23,24,26), depolarization results in fluorescence enhancement from the cell membrane whereas hyperpolarization decreases membrane fluorescence (Fig. 2C).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…2C). As predicted, and as demonstrated for previous classes of PeT-based voltage sensors (23,24,26), depolarization results in fluorescence enhancement from the cell membrane whereas hyperpolarization decreases membrane fluorescence (Fig. 2C).…”
Section: Resultssupporting
confidence: 89%
“…1) (24). PeT within a VF dye is enhanced under hyperpolarized cellular conditions (negative intracellular charge) and decreased during cellular depolarization (positive intracellular charge).…”
mentioning
confidence: 99%
“…Functionalizing the ND surface with charged molecules or polymers could provide a mechanism for such charge transfer. For example, it has been shown that electrical activity in cells can be detected by the use of voltage-dependent charge transfer from molecular wires to a fluorescent reporter (31,32). Functionalizing hydrogenated NDs with similar molecular wires could provide the necessary charge movement and allow their use as voltage indicators.…”
Section: Resultsmentioning
confidence: 99%
“…By combining this optical system with a new-generation voltage-sensitive dye (VSD), VoltageFluor (Miller et al ., 2012; Woodford et al ., 2015), fluorescence signals that encode membrane voltages with high fidelity can be simultaneously captured from neurons at different depths. We applied this pan-neuronal recording system to the nervous system of the medicinal leech, in which we elicited fictive behaviors and quantitatively manipulated membrane potential of identifiable neurons using electrophysiological methods (Tomina and Wagenaar, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These procedures were not explained in detail in our previous paper (Tomina and Wagenaar, 2017), nor in other studies using the same type of dyes (Miller et al ., 2012, Moshtagh-Khorasani et al ., 2013, Woodford et al ., 2015, Frady et al ., 2016). …”
Section: Introductionmentioning
confidence: 99%